2017
DOI: 10.1200/jco.2017.35.15_suppl.11048
|View full text |Cite
|
Sign up to set email alerts
|

Tumor volume score (TVS), modified recist, and tissue damage score (TDS) as novel methods for assessing response in tenosynovial giant cell tumors (TGCT) treated with pexidartinib: Relationship with patient-reported outcomes (PROs).

Abstract: 11048 Background: TGCT is a locally aggressive neoplasm of joint and tendon sheath synovia that may cause pain, limit joint function and destroy bone and local tissues. Measuring TGCT with RECIST is a challenge due to irregular shape and asymmetrical growth, and local tissue damage is not assessed. We reported earlier results of a longitudinal trial of pexidartinib, a selective CSF1R kinase inhibitor, using RECIST as well as novel TVS, modified RECIST and TDS. Here we examine concordance of these MRI measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For patients with TGCT, tumor response was also assessed centrally using a TVS specifically developed for this disease (8,14). For patients with TGCT enrolled after protocol amendment 8 (August 2013), we used 5 numeric rating scale (NRS) questions targeting symptoms that are relevant for patients with TGCT (i.e., worst pain, stiffness, limited motion, swelling, and instability) (15).…”
Section: Study Design Patients and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with TGCT, tumor response was also assessed centrally using a TVS specifically developed for this disease (8,14). For patients with TGCT enrolled after protocol amendment 8 (August 2013), we used 5 numeric rating scale (NRS) questions targeting symptoms that are relevant for patients with TGCT (i.e., worst pain, stiffness, limited motion, swelling, and instability) (15).…”
Section: Study Design Patients and Proceduresmentioning
confidence: 99%
“…Owing to those encouraging results as well as the lack of nonsurgical therapy options for patients with advanced diffuse TGCT, this cohort was expanded, and novel tools that might better capture TGCT-specific treatment effect, disease status, and patient-reported outcomes (PRO) were incorporated. These tools included the TVS to measure disease burden more accurately than Response Evaluation Criteria in Solid Tumors (RECIST) (8,14) and PRO (15,16) questions to measure symptom improvement; these measures were customized to capture unique aspects of TGCT. Also reported is a post-hoc analysis on the CSF1 transcript alterations in patients in the TGCT cohort.…”
Section: Introductionmentioning
confidence: 99%
“…No interaction between CSF1 and CSF1R on the neoplastic cells was found and indeed no CSF1R expression was found on the neoplastic cells, providing no support for an autocrine loop using the CSF1 pathway. Clinical trials showed that CSF1R inhibitors such as pexidartinib are effective targeted therapies for TGCT and show a reduction in tumor mass measured by MRI according to the Response Evaluation Criteria in Solid Tumors (RECIST) or TVS criteria (6, 12, 14). The lack of CSF1R on the neoplastic cells suggests that the CSF1R inhibitors target the bystander macrophages and giant cells but not the neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested that the chemoattractant and proliferative effect of CSF1 on bystander macrophages could be inhibited by drugs that interfered with the CSF1 pathway. Studies using monoclonal antibodies and small molecule inhibitors for the CSF1 pathway have shown a significant clinical effect (6)(7)(8)(9)(10)(11)(12)(13) and a decrease in tumor size as seen by an imaging measurement specifically designed for TGCT (14). It was hypothesized that the CSF1-expressing neoplastic cells might be activated through an autocrine loop by CSF1R expressed on their surface (3).…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that the chemoattractant and proliferative effect of CSF1 on bystander macrophages could be inhibited by drugs that interfered with the CSF1 pathway. Studies using mAbs and small-molecule inhibitors for the CSF1 pathway have shown a significant clinical effect ( 6–13 ) and a decrease in tumor size as seen by an imaging measurement specifically designed for TGCT ( 14 ). It was hypothesized that the CSF1-expressing neoplastic cells might be activated through an autocrine loop by CSF1R expressed on their surface ( 3 ).…”
Section: Introductionmentioning
confidence: 99%